Kegagalan Calon Incumbentcy pada Pemilihan Kepala Daerah dan Wakil Kepala Daerah di Kabupaten Indragiri Hulu Tahun 2010 - Hasanuddin; Amir Syamsuadi (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2011)
This research backgrounded by prospective drubbing politics phenomenon incumbentcy carrythe wind region at Regency Indragiri Hulu. Remembering politics force and candidate dominateincumbentcy one that huge deep win General Election competition carries the wind Region at Indonesian.Politics actor that carries self as prospective as incumbentcy on Elect carries the wind Region at RegencyIndragiri Hulu’s year 2010 experiences failing (defeat blackballs). To the effect this research main issubject to be know prospective bust causation factors incumbentcy on Elect performing carries the windRegion and Region head Representative at Regency Indragiri Hulu year 2010. Reputed theory relevantwith about problem this is cognitive about power purpose and Winning Strategy theory. Where isprospective failing incumbentcy this was analysed from that candidate trick keeps power (status quo) byuse of its politics resource as prospective as region head that officiating and also analyses on prospectiveeffort incumbentcy and its success team at deep do Winning Strategy (Political Marketing).This Observational type is observational descriptive qualitative, by use of interview datacollecting tech which is a straightforward communication with observational informan and does Question-answer that is engaged research problem, then observation to word, give, and identifies happeningphenomena, and does analisis about data which is engaged Pilkada's management and performing atRegency Indragiri Hulu Year 2010. After been done its observational, gotten by observational result, thatprospective bust factor incumbentcy caused,First, candidate incumbentcy insufficiently optimal deeputilize its politics resource as official as be of power, as frail its Mass Media Mastery, its frail is ability doesloby politics to strong party at region (Local Politics Mastery),and optimalization reducing program exploit,budget and government facility for mengkapitalisasi elector society support. Both of, Winning strategy(Political Marketing) candidate incumbentcy also under investment strength, as pattern positioning thatdon't effective, amongst those on segmentation and targeting what do just gain control governance centerregion and politics force basis traditional it just and not dominates at other region basises that becomevoice granary outgrow at Indragiri Hulu's Regency, policy one that reducing implementable baseprospective performance incumbentcy all this time. Candidate (person) candidate incumbentcy one thatreducing gets place again at society heart, try a fall supporting political party (party) one that have no termbasis outgrows at Indragiri Hulu's Regency, and push marketing that responsif's reducing and notconspicuous of elector.